Optimization of Hormonal Compositions of Media in In Vitro Propagation of Orange Cultivars from Shoot Tip Nodal Segments - Fuad Abdi; Zekeria Yusuf; Yohannes Petros; Mulugeta Desta (International Journal of Agronomy)
Orange is one of the most horticulturally important and widely cultivated Citrus species. Citrus cultivar improvement via conventional breeding strategies is normally impeded by factors related to its reproductive biology. The present study was undertaken to investigate the optimization of growth regulators’ composition of media in in vitro propagation of orange cultivar from nodal segment explants. The nodal segment explants were collected from sweet orange cultivars. The MS medium supplemented with sucrose and different concentrations of growth regulators were used for shoot proliferation and root induction. The optimum compositions of growth regulators in MS medium were assessed. The result indicated that the highest shoot response was recorded for Washington naval orange with maximum shoot proliferation rate (99.75%), shoot number per explant (3.10), shoot length (10.70 cm), leaf number per explants (12.50) after three weeks of culture. In all experiments, no growth was observed for the basal MS medium. Phytohormones combinations of indole-3-acetic acid, IAA (1.2 mg/L), and kinetin (2.0 mg/L) were found to be the best for shoot proliferation. Among the cultivars, significantly, the highest rooting rate (81.25%), root number (4.95), and root length (2.95 cm) were recorded for Washington naval orange cultivar. The least rooting rate (48.45%), root number (3.55), and root length (2.26 cm) were observed from the Valencia cultivar. Significantly, the highest rooting rate (84.90%), root number per microshoot (5.20), and root length (3.05 cm) for MS medium supplemented with 1.5 mg/L 1-naphthalene acetic acid (NAA). The comparison of different concentrations of IAA and NAA on root induction of microshoots from nodal segments of sweet orange cultivars demonstrated NAA as the more effective hormone than IAA.